2013
DOI: 10.1007/s00259-013-2525-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PET imaging with a 68Ga-labelled PSMA ligand and 18F-choline-based PET/CT for the diagnosis of recurrent prostate cancer

Abstract: PurposePositron emission tomography (PET) with choline tracers has found widespread use for the diagnosis of prostate cancer (PC). However, choline metabolism is not increased in a considerable number of cases, whereas prostate-specific membrane antigen (PSMA) is overexpressed in most PCs. Therefore, a 68Ga-labelled PSMA ligand could be superior to choline tracers by obtaining a high contrast. The aim of this study was to compare such a novel tracer with standard choline-based PET/CT.MethodsThirty-seven patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
566
1
32

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 826 publications
(617 citation statements)
references
References 29 publications
18
566
1
32
Order By: Relevance
“…Our data, based on a large and highly selected patient cohort, are in line with preliminary reports by Afshar-Oromieh (17,23). Compared with reports in the literature stating detection rates between 34% and 88% for 11 C-choline, 43%-79% for 18 F-choline, and 59%-80% for 11 C-acetate (7,(24)(25)(26)(27)(28)(29)(30)(31), 68 Ga-PSMA ligand PET/ CT offers a substantially higher detection efficacy.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our data, based on a large and highly selected patient cohort, are in line with preliminary reports by Afshar-Oromieh (17,23). Compared with reports in the literature stating detection rates between 34% and 88% for 11 C-choline, 43%-79% for 18 F-choline, and 59%-80% for 11 C-acetate (7,(24)(25)(26)(27)(28)(29)(30)(31), 68 Ga-PSMA ligand PET/ CT offers a substantially higher detection efficacy.…”
Section: Discussionsupporting
confidence: 77%
“…The recent development of 68 Ga-PSMA (Glu-NH-CO-NH-Lys-(Ahx)-[ 68 Ga(HBED-CC)]) as an extracellular PSMA inhibitor for PET imaging demonstrated a high specificity for PSMA tumor-expressing cells as well a high and specific uptake in a mouse model (16). A first preliminary study in PC patients revealed a higher image contrast and detection rate for 68 Ga-PSMA than 18 F-choline (17). In addition, further preliminary data in primary PC back the high specificity of 68 Ga-PSMA ligand PET imaging, ranging more than 95% at both patient-and fieldbased analysis for lymph node staging validated by extended pelvic lymph node dissection (18).…”
mentioning
confidence: 99%
“…125,126 In a subsequent, small clinical trial, 68 Ga-PSMA detected more lesions than 18 F-choline. 127 Somatostatin receptors are overexpressed on neuroendocrine tumor cells. Imaging of this biomarker is currently accomplished using SPECT with 111 Indiethylenetriaminepentaacetic acid (DTPA)-octreotide; however, several new radiotracers have been developed that can be imaged using PET.…”
Section: Imaging Protein and Cell Membrane Metabolismmentioning
confidence: 99%
“…[4][5][6] Here, based on our first clinical results, we describe 68Ga-PSMA-L PET/MRI as a novel imaging technique for patients with PCa at different disease stages, and discuss potential future applications.Briefly, PET/MRI was carried out on a fully integrated whole-body hybrid PET/MRI system (Siemens Biograph mMR; Siemens Healthcare, Erlangen, Germany). After intravenous injection of 122 ± 17 MBq 68 Ga-PSMA-L, a diagnostic PET-examination of the trunk (from base of skull to the proximal femur) with simultaneous acquisition of coronal T1-weighted and fat saturated axial T2-weighted images was carried out followed by a diagnostic multiparametric MR examination of the pelvis including a 15-min PET scan (mean time from injection to imaging: 51 min, range 45-63 min).…”
mentioning
confidence: 99%
“…3 Together with the novel development of combined PET/MRI, the combination of excellent morphological detail, multiparametric functional information, and molecular PET data might lead to a significant improvement in detection and staging of PCa, and thus could help to optimize oncological treatment. [4][5][6] Here, based on our first clinical results, we describe 68 Ga-PSMA-L PET/MRI as a novel imaging technique for patients with PCa at different disease stages, and discuss potential future applications.…”
mentioning
confidence: 99%